TINGKAT PENGETAHUAN DAN KEPUASAN PASIEN TERHADAP PELAYANAN SWAMEDIKASI ANTIINFLAMASI DI APOTEK WILAYAH KOTA YOGYAKARTA - Marisa Adnasari Agustina (Universitas Ahmad Dahlan, 2022)
Anti-inflammatory medicines are readily available in the community, however improper use can result in undesired side effects and a decrease in the body's basic processes. In 2021, 80.68 % of the population of DIY engaged in self- medication. Self-medication behavior is heavily influenced by drug use information knowing. This study aimed to examine the level of knowledge and patient satisfaction with anti-inflammatory self-medication services at a drugstore in Yogyakarta. This research was a descriptive observational study employing a cross- sectional design. This study's samples consisted of patients and their families who purchased anti-inflammatory medications at pharmacies in the city o